Assessment of coal pyrolysis kinetics for Barracuda or Ansys Fluent. (February 2019) - Krusch, S.; Scherer, V.; Solimene, R.; Senneca, O.
Abstract: In the present work different methodologies have been used to analyze pyrolysis of a German bituminous coal "Auguste Victoria" with the aim to obtain pyrolysis kinetic submodels suitable for combustion models developed under Barracuda or other CFD environment such as Ansys Fluent. Intrinsic kinetics have been obtained by conventional TGA analysis at low heating rate (2–20 K/min) and with small particle size (in the order of 0.1 mm) and described by a two-step pyrolysis model. Additionally, the rates of pyrolysis were measured under fluidized bed conditions for larger particle size fractions using a method based on the time-resolved measurement of pressure in the freeboard induced by volatiles release and by a flow restriction at the exhaust. Results of thermogravimetric experiments have been worked out to obtain submodels of coal pyrolysis, comparing and discussing alternative reaction networks of different complexity. However, in fluidized bed experiments, using larger particle sizes, transport limitations become important. As expected, for this regime the reactions rates become lower the larger the particle size, reducing the relevance of intrinsic kinetic submodels.